Managing a child with cherubism with functional consequences: a case report - Mehra, Manisha; Joshi, Poonam; Das, Aditi; Bhowmick, Rohit; Bhunia, Niladri Sekhar; Dutta, Atanu Kumar (International Journal Of Community Medicine And Public Health, 2025)
Cherubism is a rare begin, self-limiting autosomal dominant disorder characterized by bilateral and symmetric fibro-osseous lesions affecting the mandible and maxilla. The child with this disorder requires conservative management. Surgical interventions such as contouring, resection, or curettage are rarely required for disease and only in severe functional problems. This case study attempts to address the physical and psychological issues and challenges the child and his family members face.